Advances in fenugreek breeding: novel genetic and omic approaches - Bal, Solanki; Sharangi, Amit Baran; Saeed, Mohd; Alkhathami, Ali; Siddiqui, Samra; Alabdallah, Nadiyah M. (Frontiers in Plant Science, 2025)
Fenugreek (Trigonella foenum-graecum L.) has long been valued for its diverse applications in culinary, medicinal, and cultural traditions across the globe. In recent years, this underutilized legume has attracted growing attention from researchers due to its rich profile of bioactive compounds and its potential in sustainable agriculture and health-based industries. Despite its historical significance and remarkable adaptability to different agro-climatic zones, fenugreek has not received adequate focus in mainstream breeding programs. However, recent developments in genetic improvement strategies, mutation breeding, molecular markers, and biotechnological techniques have started to unlock its untapped potential. This review brings together the latest advancements in fenugreek research, ranging from conventional breeding methods to cutting-edge molecular and omic approaches. Mutation breeding using physical and chemical mutagens like EMS and sodium azide has played a significant role in generating phenotypic variability and improving key traits such as yield, early maturity, and secondary metabolite concentration. Marker-assisted analysis using RAPD, AFLP, ISSR, and combined systems has contributed to mapping genetic diversity and identifying promising genotypes. Alongside these, the use of tissue culture techniques-including callus culture, cell suspension, protoplast regeneration, and organogenesis-has facilitated in vitro propagation and enhanced the synthesis of valuable phytochemicals like diosgenin and trigonelline. Furthermore, genetic transformation via Agrobacterium rhizogenes has enabled the development of hairy root cultures, which serve as efficient systems for bioactive compound production. The integration of omics technologies-genomics, transcriptomics, proteomics, and metabolomics-has offered new insights into the molecular basis of trait expression, metabolic pathways, and regulatory networks involved in fenugreek’s therapeutic potential. Notably, transcriptome studies have advanced our understanding of steroidal saponin biosynthesis, while metabolomic and proteomic tools have provided dynamic perspectives on plant physiology and compound accumulation under different conditions. Altogether, these advancements highlight a multidimensional approach to fenugreek improvement, paving the way for the development of elite cultivars with enhanced agronomic performance, higher nutritional and pharmaceutical value, and greater resilience to environmental stresses. This comprehensive overview underscores the need for continued investment in interdisciplinary research to fully harness the potential of fenugreek as both a functional food and a medicinal crop for the future.